Influence of Female Teachers’ Reproductive Health Experiences on Their Work Performance in Schools - Tuhiriirwe, Hellen; Sekiwu, Denis (Canadian Journal of Educational and Social Studies, 2021)
In this article, I discussed the influence of female teachers’ reproductive health experiences on their work performance in schools. By natural course, females undergo reproductive health changes such as menstruation periods, pregnancy, childcare and nursing which tend to weaken them physically, psychologically and mentally because of the challenges they encounter. This study was carried out to explore the influence of female teachers’ reproductive health experiences on their work performance and the coping mechanisms they use while executing their duties and responsibilities. In total, a sample of 45 respondents was selected using purposive sampling. These included Headteachers, Heads of Department, Male teachers and Female teachers. The study employed Qualitative techniques by adopting a phenomenological research design to collect and analyse data. Data collection tools used were the Interview guide, Focus group discussion guide and Documentary review checklist. A qualitative presentation and analysis of data were based on themes formulated based on study objectives. The cultural feminist theory was used to interpret and discuss data. The study findings indicate that female teachers are stigmatized, oppressed, stereotyped and discriminated against at the workplace. These findings are of great importance to the Ministry of Education, school administrators and future researchers as they will guide policy formulation to improve the welfare of female teachers at the workplace. The state through the Ministry of Education and Sports should formulate a public policy agenda on gender equity to promote the welfare and inclusion of female teachers in all departments at the workplace. Keywords: Female Reproductive Health Experiences, Work Performance.
Keywords: Female Teachers; Reproductive Health Experiences; Schools